2014
DOI: 10.1002/chem.201405167
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Sensitive Aqueous‐Phase Detection of 2,4,6‐Trinitrophenol (TNP) by an Amine‐Functionalized Metal–Organic Framework

Abstract: Highly selective and sensitive aqueous-phase detection of nitro explosive 2,4,6-trinitrophenol (TNP) by a hydrolytically stable 3D luminescent metal-organic framework is reported. The compound senses TNP exclusively even in the presence of other nitro-compounds, with an unprecedented sensitivity in the MOF regime by means of strategic deployment of its free amine groups. Such an accurate sensing of TNP, widely recognized as a harmful environmental contaminant in water media, establishes this new strategic appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
133
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(146 citation statements)
references
References 51 publications
12
133
1
Order By: Relevance
“…Resonance energy transfer is one more effective fluorescence quenching mechanism, often ascribed for such PL-quenching responses. [86][87][88] In fact, the non-linear SV plot for TNP substantiates the presence of long range resonance energy transfer. The effectiveness of the energy transfer significantly relies on the extent of spectral overlap between the emission spectra of the fluorophore and the absorption spectra of the concerned nonemissive analyte.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Resonance energy transfer is one more effective fluorescence quenching mechanism, often ascribed for such PL-quenching responses. [86][87][88] In fact, the non-linear SV plot for TNP substantiates the presence of long range resonance energy transfer. The effectiveness of the energy transfer significantly relies on the extent of spectral overlap between the emission spectra of the fluorophore and the absorption spectra of the concerned nonemissive analyte.…”
Section: Resultsmentioning
confidence: 72%
“…These features result in the rational design and study of MOF materials for the desired selective detection of cations, anions, small molecules, explosives and biomolecules. 13,48,80,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In view of the targeted selective TNP detection in water by MOFs with high sensitivity, regardless of the latest advances, the reports of fluorescent MOFs exhibiting selective and sensitive TNP detection in concurrent presence of other nitro analytes are only few, while most of the reported MOFs involve detection only in organic/ organic-water mixture phase. 86 Subsequent to the discovery of the key role of lewis basic pyridyl functionality behind selective aqueous-media TNP sensing; 88 as a first-of-its kind approach, very recently, our group had come up with two reports of aqueous phase selective TNP-sensing based on two different MOF compounds.…”
mentioning
confidence: 92%
“…. 179 Preliminary tests revealed that bio-MOF-1 immersed in water for several weeks retains its crystallinity, confirming its hydrolytic stability. The reported MOF also showed identical stability in TNT solution: the free amine groups located into the pores of bio-MOF-1 ensure an easy and strong interaction with the guest TNT molecules.…”
Section: -Luminescencementioning
confidence: 89%
“…22 Luminescent MOFs have been over the years constructed from the self-assembly of very distinct organic linkers and metallic centres (lanthanides and transition metals). Some of them exhibit great potential to be applied as sensors to detect VOCs and explosive molecules, [179][180][181][182][183][184] ions, [185][186][187][188] pH sensors, 189 for bioimaging and intracellular sensing 187 and to produce luminescent nanothermometers to be used in nanotechnology and biomedicine. 191 Even though the new dpNDI linker predictably has a low fluorescence quantum yield, the authors deduced that this molecule could strongly interact with aromatic VOCs.…”
Section: -Luminescencementioning
confidence: 99%
“…The synthesis of new coordination polymers (CPs) or metal organic frameworks (MOFs) has captured researchers' interest owing to the variety of compositions and topologies of the produced compounds [1][2][3][4][5][6][7][8][9] together with their interesting functional properties and applications [10][11][12][13][14][15][16][17][18][19][20]. The properties of such systems are controlled by their chemical composition and structure, which are easily monitored by simply varying the reactants and reaction conditions.…”
Section: Introductionmentioning
confidence: 99%